Beyond Biodiversity and Species: Problematizing Extinction. (September 2016) - Mitchell, Audra
Scientific and public discourses on the current mass extinction event tend to focus their attention on the decline of 'species' and 'biodiversity'. Drawing on insights from the humanities, this article contends that the processes of extinction also produce a diverse range of subjects. Each of these subjects, it argues, raises specific ethical challenges and creates opportunities for cosmopolitical transformation. To explore this argument, the article engages with several subjects of extinction: 'species' and 'biodiversity'; 'humanity'; 'unloved' subjects; and absent or non-relational subjects. In each case, it examines how attention to these subjects can highlight the exclusions and inequalities embedded in dominant discourses, and to identify possibilities for plural ethico-political responses to mass extinction.